Synthetic Musk Compounds in Human Biological Matrices: Analytical Methods and Occurrence—A Review. (7th December 2020) - Katuri, Guru Prasad; Fan, Xinghua; Kosarac, Ivana; Siddique, Shabana; Kubwabo, Cariton
Abstract: Extensive use of synthetic musk compounds (SMs) in numerous consumer and personal care products has resulted in direct human exposures via dermal absorption, inhalation of contaminated dust and volatilized fragrances, and oral ingestion of contaminated foods and liquids. SMs and their metabolites are lipophilic, hence commonly detected in various biological matrices such as blood, breast milk, and adipose tissue. Appropriate analytical techniques are needed to detect and quantify SMs in biological matrices to assess their potential effects on human health. Different methods to process and analyze SMs in biological matrices, including sample-pretreatment, solvent extraction, cleanup, and instrumental analysis, are presented in this review. The concentration levels of selected musk compounds in biological samples from different countries/regions are summarized. Finally, research gaps and questions pertaining to the analysis of SMs are identified and suggestions made for future research studies.